Politik Anti Neoliberalisme Venezuela di Era Kepemimpinan Presiden Nicolás Maduro - Nur Aisyah Yusran (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2026)
This study examines how Nicolás Maduro's anti-neoliberal politics in Venezuela triggered a systematic securitization process by the US from 2014 to 2026. Drawing on Securitization Theory (Buzan et al., 1998) and a Neo-Gramscian perspective (Cox, 1981), this study argues that Maduro's anti-neoliberal policies constitute a counter-hegemonic challenge created by the United States. This threat is framed as a threat to democracy, regional security, and ultimately the narco-state, ultimately leading to the military intervention of January 2026. Economic sanctions failed to pressure the regime, exacerbated the humanitarian crisis, and set a dangerous precedent for the norm of state sovereignty in international law, suggesting that this securitization process proved ineffective. By addressing temporal and conceptual gaps in previous research, this study adds to the Security Studies literature. This study also highlights implications for international law, regional stability in Latin America, and the broader debate on securitization practices in contemporary global politics and US foreign policy strategy and international security governance frameworks debates.